The effect of transcutaneous electrical nerve stimulation (TENS) on pain control and phenylethanolamine-N-methyltransferase (PNMT) gene expression after cesarean section - Chen, Wenxiang; Liu, Chunying; Yang, Yongrong; Tian, Lili (Cellular and Molecular Biology, 2021)
Transcutaneous electrical nerve stimulation (TENS) is one of the non-pharmacological methods of pain relief that has been able to reduce pain by 70 to 90% in postoperative pain control. This study aimed to determine the effect of TENS on pain control after cesarean section and its effect on PNMT gene expression. For this purpose, a double-blind randomized clinical trial was performed on 70 Chinese patients with elective cesarean section. Patients were divided into case and control groups. In the case group, TENS and analgesic drugs were used to relieve pain, and in the control group, the only analgesic drug was used. Then the severity of pain, recurrence of pain attacks, the number of analgesic drugs used and the amount of analgesic drug used in the first 24 hours after surgery were evaluated and compared. Blood samples were also taken from patients to evaluate PNMT gene expression. The semi-quantitative RT-PCR was used to study changes in gene expression. The results showed that the group treated with TENS had less pain intensity and less recurrence of pain attacks than the group that received only analgesic medication. Also, the frequency of analgesic drug use and its dose in the TENS group were significantly lower than in the control group. TENS, on the other hand, has been able to greatly reduce the expression of the PNMT gene, which is produced during times of stress. Therefore, it is recommended that TENS be used as a non-invasive and non-pharmacological adjuvant effective in reducing pain after cesarean section.